Pemodelan Robot Beroda Menggunakan Umpan Balik Giroskop - Aulia Rahman (Jurnal Rekayasa Elektrika, 2016)
Modeling of a system is an important step for designing a good controller for a wheeled mobile robot. There are several techniques can be used gaining a model. One is deriving an analytical model mathematically. Another technique is by using system identification where the robot is given an input test signal and then measured the output signal. This technique, in general, is simpler compared to the analytic one. This paper described the modeling of a wheel mobile robot and used a gyroscope sensor as a feedback.The transfer function model of the robot is a second order system.